INTERACTION OF THE STRUCTURE OF WORLD AND LIFE POSITION - Toshpulatovich, Mamatkulov Sanjar (International Journal of Psychosocial Rehabilitation, 2020)
The worldview and related issues have always been in the focus of various disciplines. When a person, an individual, a particular group and society as a whole become the object of research, the issue of self- concept is also mentioned. The worldview, which is an interdisciplinary concept, is studied from different perspectives in the fields of philosophy, psychology, sociology, culturology, anthropology, pedagogy and many others. For example, worldview in psychology is studied as a phenomenon in psychology, behavior in sociology, cultural phenomenon in culturology, ethnocultural image in anthropology, as an object of education in pedagogy. However, the very essence, structure and functional aspects of the worldview are fully and completely embedded within philosophy. Philosophy can, by its universalist character, provide ontological, gnoseological, axiological, praxiological, and other aspects of this phenomenon and give conceptual and methodological guidance to other subjects in this regard. Nevertheless, the issue of worldview is, among other universal problems of philosophy, one of the problems which has not yet been fully resolved. The point is that the worldview is extremely complex and multifaceted. It is difficult to come to a clear understanding of its structure, functional and structural analysis. Therefore, in this article, we will look at some of the worldview studies and try to identify its structure and components. At the same time, we critically analyze existing philosophical ideas so far and draw attention to some gaps and ambiguities. We also examine how the worldview relates to the individual, his or her life position.